Three Novel Transition Metal with Ethylenediamine Complex Template Polyborates [Pt(en)3]4 [B5O6 (OH)4] Cl15, [Rh(en)3][B5O6 (OH)4]3∙ 10H2O, and [Zn(en)3] [B6O7 (OH) 6]· 2H2O have been Synthesized and Characterized by Elemental Analysis, FT-IR, H, 13C, 11B - NMR, TGA-DSC, Powder X-ray Diffraction and Magnetic Properties - Mohammed A. Altahan (Journal of Global Pharma Technology, 2018)
Three new polyborate compounds [Pt(en)3]4[B5O6(OH)4]Cl15(1), [Rh(en)3][B5O6(OH)4]3∙10H2O(2), and [Zn(en)3][B6O7(OH)6]·2H2O (3)have been prepared. The new compounds have been identified by elemental analysis, FT-IR, H, 13C, 11B - NMR, TGA-DSC, powder X-ray diffraction and magnetic properties. The three new compounds are consisting of transition metals (platinum (IV), rhodium (III), and zinc (II)) cations, polyborate ([B5O6 (OH)4]-and [B6O7(OH)6]2-) anions, and lattice water molecules.Keywords: polyborate, zinc (II), platinum (IV), rhodium (III).